A competence-time-quality scheduling model of multi-skilled staff for IT project portfolio. (January 2020) - Chen, Rong; Liang, Changyong; Gu, Dongxiao; Zhao, Huimin
Highlights: We propose a multi-objective portfolio scheduling and staff assignment model. The objectives are skill enhancement, development cycle time, and product quality. The model incorporates skill cultivation through a learning curve. We propose a Pareto ant colony optimization algorithm combining genetic operators. Personalized decision rules are discussed for selecting a good Pareto solution. Abstract: Technical professionals are a key factor for IT product development. In an IT company, it is common for an employee to hold multiple skills. Multi-skilled staff increases the difficulty of project portfolio scheduling and staff assignment. This paper helps R&D managers cope with the problem by proposing a multi-objective optimization model of project portfolio scheduling and multi-skilled staff assignment. The model considers three objectives with strong practicality, i.e., staff skill enhancement, development cycle time, and product quality, and incorporates skill cultivation through a learning curve. We then propose an improved multi-objective Pareto ant colony optimization algorithm combining genetic operators to find an approximate Pareto solution set. Personalized decision rules with strong practicability are also discussed for selecting an appropriate solution. A case study in a leading electrical device company in China demonstrates the utility of the proposed model and algorithm.